Fun Learning in Science Teaching in the Early Years of Elementary School (Research, Society and Development, 2022)
In most Brazilian schools, teaching is centered on the figure of the teacher as a defender of all knowledge, where a traditional tendency predominates and is almost always based on the textbook, not allowing the free participation of the student. Science teaching, in turn, must be worked in a different way, through practical classes and diversified activities that can engage students and motivate them for classes. In this sense, this work brings a reflection about the actions and methodologies that can be developed and used by teachers in the area of Sciences. Therefore, the objective of this article is to analyze the importance of science classes being worked in a fun way, as well as suggesting ideas to educators, so that they can make their students' learning fun and their classrooms more welcoming environments, with more dynamic and attractive classes. After all, the child needs the scientific initiation process to occur in a pleasant and motivating way. Therefore, a qualitative bibliographic research was developed. Data analysis followed the assumptions of Laurence Bardin's content analysis. As a result, we show that many actions can be done by teachers so that students are interested in participating in classes. As well as different methodologies and activities can be used to streamline the teaching and learning process.